Lecturers’ Utilization of Government Electronic Documents for Research in Nigerian Universities - Mesagan, Olanike Faith; Twinomurinzi, Hossana (Studies in Learning and Teaching, 2025)
The importance of government publications in meeting today's information needs cannot be overstated. This research sought to examine the utilization of government e-documents by lecturers in Nigerian universities. The research was directed by four specific objectives and two hypotheses, utilizing a descriptive survey research design. The population is 642 academic staff from the three universities. Questionnaires were used and analyzed using mean and standard deviation. Findings indicated that lecturers use shelves, printout indexes, open access, and librarian assistance to access government documents from Nigerian university libraries. Documents were used for historical, cultural, political, statistical, legal, and government research-related purposes. Challenges identified include the lack of digitization of government documents, poor documentation, and organization hindering their utilization. The study also found that the years of experience of lecturers significantly influenced their mode of accessing government documents (P = 0.003), while educational level/qualification significantly influenced the areas in which government documents were used by the lecturers (P = 0.000). Recommendations included improved digitization of government e-publications, encouraging more academic staff to utilize these resources in their research, improving the documentation of government e-documents, and fostering strong relationships between academic staff and librarians.